Gender in world history - Stearns, Peter N., author.
1 online resource.
Keywords: "Gender in World History integrates gender history and world history by dealing with significant global changes over time, regional patterns of gender relations, and the results of interregional contact on gender roles and concepts. Now in its 4th edition, this volume explores the rise of patriarchal gender systems and, in more modern history, the gradual and checkered decline of these systems. In addition to the roles of agriculture and then industrialization in shaping gender relations, the book deals with the impact of major religions, imperialism and decolonization, and human rights movements in more recent history. Regional coverage includes East Asia, South Asia, the Middle East and Mediterranean, Sub-Saharan Africa, Europe and the Americas. The book seeks to show how major patterns and changes in the past shed light on current gender issues in many world regions, enabling students to understand how gender roles have varied across the world and over time. This new edition also includes: More material on several societies, particularly in Asia and the Middle East. Greater attention on historical and comparative assessment of sexual identities A focus on basic features of gender configurations Discussions of more recent human rights movements Providing a global but succinct overview of the history of gender throughout the world, Gender in World History remains essential reading for students of world history and gender studies"--